Membangun Motivasi Belajar Peserta Didik SD pada Masa Pandemi Menggunakan Reward - Irmawati, Wahyu (Universitas Sebelas Maret, 2020)
Learning during the Covid-19 pandemic demands to create innovation and creativity in supporting the online learning process. The reality is that a lot of learning received by students is monotonous only in the form of assignments without any feedback or reinforcement of student learning outcomes. This causes students to become bored, lack enthusiasm in learning, and many students prefer to play rather than study during a pandemic because there is no motivation or reinforcement from the teacher. Giving rewards is very important given by teachers to students as feedback, reinforcement and appreciation because students have been willing to learn every day. Teachers should strive to provide rewards in innovative forms so that students feel interested and happy in learning. Rewards can be in the form of words of praise, giving a score of 100, a thumb sticker, a smile or other sign of encouragement that the teacher can give to students to raise enthusiasm for learning.